2018
DOI: 10.22161/ijeab/3.4.42
|View full text |Cite
|
Sign up to set email alerts
|

Study on heavy metals levels and its risk assessment in edible fish (Himantura imbricate) from Persian Gulf

Abstract: Heavy metals are contaminants of great environmental concern due to their multiple origins (natural and anthropogenic), the ability to accumulate in organs and tissues, and the deleterious effects they can cause in organisms. Studies on the accumulation of metals in seafood, such as fish, have increased in importance due to the risk for human health when consuming fish contaminated by metals. The present work was aimed at verifying the concentrations of cadmium (Cd), Nickel (Ni) and lead (Pb) in the muscular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results of the study, which revealed that certain cases surpassed the allowable limits for the concentrations of heavy metals in both water and plants, highlight the necessity of monitoring heavy metal pollution and its possible effects on ecological resilience and human health [72]. Additionally, a study looking at the levels of heavy metals and risk assessment in edible fish from the Persian Gulf found considerable regional variability in heavy metal concentrations [73]. Management procedures, wastewater discharge, and industrial activity are some of the causes of these variances.…”
Section: Heavy Metalsmentioning
confidence: 94%
“…The results of the study, which revealed that certain cases surpassed the allowable limits for the concentrations of heavy metals in both water and plants, highlight the necessity of monitoring heavy metal pollution and its possible effects on ecological resilience and human health [72]. Additionally, a study looking at the levels of heavy metals and risk assessment in edible fish from the Persian Gulf found considerable regional variability in heavy metal concentrations [73]. Management procedures, wastewater discharge, and industrial activity are some of the causes of these variances.…”
Section: Heavy Metalsmentioning
confidence: 94%